2020
DOI: 10.21776/ub.jitek.2020.015.02.5
|View full text |Cite
|
Sign up to set email alerts
|

The Substitution Effects of Tapioca Starch and Beetroot Powder as Filler On The Physical and Sensory Characteristics Of Chicken Sausage

Abstract: Red beetroot is rich in phenolic acids and betalain as natural food-coloring agents. Freeze-dried red beetroot that ground into powder can be used as a source of natural coloring to substitute the use of synthetic food color additives as well as filler to substitute tapioca. This study evaluates the function of red beetroot powder not only as filler but also as coloring agent on chicken sausage. Furthermore, its effects as filler (tapioca and beetroot) were also observed on the physical and sensory characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Similarly, the use of beetroot powder increased color scores but did not influence the overall acceptability of sausages [8]. The results presented in this study [8] agreed with those reported by other authors, who reported that chicken sausages reformulated with beetroot powder resulted in a higher color (due to the highest red color) and lower flavor scores (due to the earthy taste of beetroot powder) than control samples, while the inclusion of beetroot powder did not affect the overall acceptability [67].…”
Section: Application Of Beetroot In Meat Productssupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, the use of beetroot powder increased color scores but did not influence the overall acceptability of sausages [8]. The results presented in this study [8] agreed with those reported by other authors, who reported that chicken sausages reformulated with beetroot powder resulted in a higher color (due to the highest red color) and lower flavor scores (due to the earthy taste of beetroot powder) than control samples, while the inclusion of beetroot powder did not affect the overall acceptability [67].…”
Section: Application Of Beetroot In Meat Productssupporting
confidence: 90%
“…In contrast, the effect of the use of dehydrated beetroot showed contradictory results for pH values. The influence of the direct addition of beetroot powder was studied in emulsified sausages [8,65,66], fermented sausages [46,68], and boiled sausages [66,67]. The use of 0.25-0.5% [65], 0.5-1% [46], and 2-6% [68] of beetroot powder decreased pH, while the use of 0.5-1% of powdered beetroot did not affect [66,67] or increase [8] the pH values of sausages.…”
Section: Application Of Beetroot In Meat Productsmentioning
confidence: 99%
“…As the percentage of red beet flour increased, it was shown to increase the water holding capacity of corned chicken, this was because red beet b, c, d Several superscripts in the same column showed a highly significant difference (P < 0,01) from the color L* a* b* of corned chicken. flour had a larger particle size than tapioca flour, thereby increasing the water holding capacity [18]. The pH value can affect the water holding capacity.…”
Section: Water Holding Capacitymentioning
confidence: 99%
“…Swastike et al [49] studied the effects of the addition of beetroot powder on the sensory characteristics of chicken sausages with tapioca flour as filler. Four ratios of beetroot powder and tapioca were used: 18:0, 17:1, 16:2, and 15:3 [%:%].…”
Section: Effect Of Polyphenolic Extract and Dyes On Sensory Evaluation Of Sausagesmentioning
confidence: 99%
“…Overall, in terms of flavor, odor, color, and appearance, the sausages with C. incanus extract and lycopene (CLS) and the sausages with 2% curing salt (NS) were rated the highest. Swastike et al [49] studied the effects of the addition of beetroot powder on the sensory characteristics of chicken sausages with tapioca flour as filler. Four ratios of beetroot powder and tapioca were used: 18:0, 17:1, 16:2, and 15:3 [%:%].…”
Section: Effect Of Polyphenolic Extract and Dyes On Sensory Evaluation Of Sausagesmentioning
confidence: 99%